ANALISIS KOMPONEN DAYA TARIK WISATA SENI PAGELARAN WAYANG KULIT DURASI SINGKAT DI MUSEUM SONOBUDOYO YOGYAKARTA - , PURWADHANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Shadow puppet is one of the nationâs cultural heritage which able to survive form time to time with changes and development until now. Currently the puppet role and function is no longer focussed only in the religious ceremonies, but it already shift to entertaintment event which prioritize the core of story with cultural values and various art elements which all of the are coalesce in the shadow puppet performance. Even now the shadow puppet performance becomes one of the tourism attraction in Yogyakarta which still prioritize cultural tourism as the city icon. Sonobudoyo Museum has already started the short in time of shadow puppet performance since 1989 and the museum administrator commited to will always shew the short duration of shadow puppet performance as one of the prime tourist attraction in Sonobudoyo Museum of Yogyakarta. The art performance in the context of tourism industry has become the important and interesting tourist attraction, especially if it associated with cultural tourism activity. The art performance to cultural tourism attraction package has several attraction components which constitute as the benchmark of a traditional art performance whether it will able to attracting tourist interst to watch or not, including duration, story, presentation of the show, and show schedule. From all of these tourism attraction components, it will be analyzed used comparative study to other same forms of tourism attraction in Yogyakarta.